A study of Hong Kong undergraduate students’ use of DeepSeek - Gaspar, Wong Ching Ho; Bosco, LI Sui Sum (Asian Journal of Contemporary Education, 2025)
The study explores how Hong Kong undergraduate students utilize DeepSeek in their academic endeavors. Existing literature predominantly focuses on ChatGPT in tertiary education, leaving a research gap regarding DeepSeek’s usage among undergraduate students in Hong Kong. This study employs the theoretical framework of ’Philosophers of Technology’ as a guiding lens. The methodology involves a modified technolinguistic biography. This study has modified the original biography for AI-situated literacy studies and conducted the AI-technobiography in interview format. This study aims to investigate: 1) how Hong Kong undergraduate students use DeepSeek in their studies, if at all, and 2) the impacts of DeepSeek on the studies of Hong Kong undergraduate students. Findings show that: 1) students deploy DeepSeek to facilitate essay writing, look for definitions of academic jargon, and summarize course readings; and 2) the emergence of DeepSeek has sparked opportunities for them to reflect upon the ethical implications of generative AI. This study enhances the original theoretical framework of "Philosophers of Technology" by advocating a new category: "youth/students as philosophers-practitioners." The study modifies the ethnographic approach and demonstrates the viability of adapting and deploying ethnographic methods originally designated for digital literacy studies into AI-mediated literacy studies.